De NUTS II à euro-région : le parcours de la Galice dans l’Union européenne - Luis Domínguez Castro (Cahiers de Civilisation Espagnole Contemporaine)
Galicia is an old European cultural nation. It is also a Spanish Autonomous Community, endowed with self-government since 1981, which joined the European Communities in 1986, becoming a NUTS II. It has been an important beneficiary of European structural funds that have helped it to converge in GDP with the Spanish and European Union averages. At the same time, it has developed an outstanding foreign action with the North of Portugal that has been taking shape in the configuration of an Euroregion.